Responding to the marauding terror attack: the police perspective. Issue 2 (16th July 2018) - Wheatley, Sean; Hollingsworth, A C; Greaves, I
Abstract : UKpolice forces have had to adapt their tactical approach to the emerging terror threat that now faces the UK. This has led to an evolution in the training, education and conduct of authorised firearms officers and an increased capability in the provision of immediate lifesaving care to injured casualties. This article intends to describe the police response to a marauding terror attack and describes the medical capabilities authorised firearms officers possess in order to educate other emergency service responders to such an event. The challenges of training for a major terrorist event and the benefits of collaborative working with other emergency service personnel are discussed.